Conflict Management In Increasing Organizational Productivity (Research At Insan Cendekia Mandiri University Bandung and Mandiri University Subang) - Dedeng Juheri; Ulfiah; Hendi S; Muchtar; Deti Rostini (Departement Of Master Of Islamic Education Graduate Programme Sultan Muhammad Syafiuddin Institute Of Islamic Studies Sambas, Indonesia, 2022)
Conflict management in increasing organizational productivity includes planning, organizing, implementing, monitoring, constraining and resolving conflicts. The general purpose of this research is to identify, examine and describe conflict management in increasing organizational productivity. The results showed: a) Planning, includes identifying the causes of conflict, including differences in thinking, different views, differences in understanding, leadership styles, character of leaders and managerial abilities of leaders in managing the organization; b) Organizing, includes the types of conflicts within the organization, including internal conflicts, conflicts between individuals and conflicts between groups; c) Implementation, through preventing, avoiding, handling, resolving and creating conflicts; d) Supervision of conflict management through the establishment of rules, policies, and evaluations; e) Constraints, consist of internal factors, including human resources that have not been maximized, parties who are allergic to change, rules that have not been steady, leadership ambitions, conflicts of interest, the campus is not compact with foundations and external factors include social, political changes and economy so as to cause disruption of organizational activities; f) Solutions, through raising awareness, reducing conflict, negotiating and reaching agreement. In conclusion, a well-managed conflict can generate ideas, motivation and inspiration in increasing organizational productivity.